Myostatin and muscle atrophy during chronic kidney disease - Bataille, Stanislas; Chauveau, Philippe; Fouque, Denis; Aparicio, Michel; Koppe, Laetitia (Nephrology, dialysis, transplantation, 2021)
Chronic kidney disease (CKD) patients often exhibit a low muscle mass and strength, leading to physical impairment and an increased mortality. Two major signalling pathways control protein synthesis, the insulin-like growth factor-1/Akt (IGF-1/Akt) pathway, acting as a positive regulator, and the myostatin (Mstn) pathway, acting as a negative regulator. Mstn, also known as the growth development factor-8 (GDF-8), is a member of the transforming growth factor-β superfamily, which is secreted by mature muscle cells. Mstn inhibits satellite muscle cell proliferation and differentiation and induces a proteolytic phenotype of muscle cells by activating the ubiquitin-proteasome system. Recent advances have been made in the comprehension of the Mstn pathway disturbance and its role in muscle wasting during CKD. Most studies report higher Mstn concentrations in CKD and dialysis patients than in healthy subjects. Several factors increase Mstn production in uraemic conditions: low physical activity, chronic or acute inflammation and oxidative stress, uraemic toxins, angiotensin II, metabolic acidosis and glucocorticoids. Mstn seems to be only scarcely removed during haemodialysis or peritoneal dialysis, maybe because of its large molecule size in plasma where it is linked to its prodomain. In dialysis patients, Mstn has been proposed as a biomarker of muscle mass, muscle strength or physical performances, but more studies are needed in this field. This review outlines the interconnection between Mstn activation, muscle dysfunction and CKD. We discuss mechanisms of action and efficacy of pharmacological Mstn pathway inhibition that represents a promising treatment approach of striated muscle dysfunction. Many approaches and molecules are in development but until now, no study has proved a benefit in CKD.